Identifying and characterising the Plasmodium falciparum merozoite surface protein 10 Plasmodium vivax homologue (2005)
Plasmodium vivax malaria is one of the most prevalent parasitic diseases in Asia and Latin-America. The difficulty of maintaining this parasite culture in vitro has hampered identifying and characterising proteins implied in merozoite invasion of red blood cells. We have been able to identify an open reading frame in P. vivax encoding the Plasmodium falciparum merozoite surface protein 10 homologous protein using the partial sequences from this parasites genome reported during 2004. This new protein contains 479 amino-acids, two epidermal growth factor-like domains, hydrophobic regions at the N- and C-termini, being compatible with a signal peptide and a glycosylphosphatidylinositol anchor site, respectively. The protein is expressed during the parasites asexual stage and is recognised by polyclonal sera in parasite lysate using Western blot. P. vivax-infected patients sera highly recognised recombinant protein by ELISA.